Perception of work in the IT sector among men and women—A comparison between IT students and IT professionals - Pyrkosz-Pacyna, Joanna; Dukala, Karolina; Kosakowska-Berezecka, Natasza (Frontiers in Psychology, 2022)
Lack of gender balance within STEM fields is caused by many factors, some of which are related to the fact that women do not perceive certain occupations as congruent with their career and personal goals. Although there is a large body of research regarding women in STEM, there is a gap concerning perception of occupations within different STEM industries. IT is a domain where skilled employees are constantly in demand. Despite the fact that the overall female representation in STEM fields is rising and that the IT industry is conducting numerous interventions in order to attract women to careers in IT, the representation of women in this domain is still disappointingly low. Therefore the goal of our study was to examine the differences among male and female IT and non IT students and employees in terms of their perception of IT and other factors influencing the feeling of aptness of IT: goal congruence, sense of belonging and self-efficacy. In this paper we present the results of a study conducted among working IT professionals (N=205) and IT students (N=127) that we compare with individuals from non-IT sectors (N = 222 employees, 107 students). Our results showed significant gender differences between IT students and professionals. We found that communal goals are more important for IT employees than for IT students (both male and female) and that sense of social belonging is stronger among female than male IT employees and students. Women employed in IT also had the same level of sense of social belonging as women in non-IT group. These findings suggest that after entering IT positions, women’s perception of the domain might become potentially more favorable and attuned with their needs. We also found that female IT students value agentic goals more than communal goals which was not the case for female IT employees. The results highlight the importance of investigating women’s perception of the IT sector at different levels of career in terms of their goals and other work-related variables. Such lines of research will help develop more effective interventions in attracting women to enter the IT field.